'It's who we are': eco-nationalism and place in contesting deep-sea oil in Aotearoa New Zealand. (2nd July 2016) - Diprose, G; Thomas, AC; Bond, S
ABSTRACT: Given near consensus among the scientific community about the anthropogenic nature of climate change, there is pressing concern about how to mobilise enough people to care and demand wider socio-political change. In this article we explore this urgent issue, drawing on recent conflicts over deep-sea oil exploration and drilling in Aotearoa New Zealand. We explore how some activist groups are attempting to mobilise care and concern around deep-sea oil drilling and climate change through the use of narratives that entwine aspects of national identity with the non-human world. We suggest that these activist groups are not concerned about a retreat of the state, but rather, are in direct conflict with the state, and state interventionism, over fossil fuel development trajectories in Aotearoa New Zealand. In drawing upon eco-nationalism, and particularly a way of life related to place, activists have called into question the common sense of business as usual and thereby sought to expand space for 'ordinary' Aotearoa New Zealanders to care about climate change.